Employers' Perspectives on the Use of Medical Assistant Apprenticeships: A Qualitative Study. Issue 3 (July 2022) - Jopson, Andrew D.; Cummings, Allison G.; Frogner, Bianca K.; Skillman, Susan M.
Abstract : Medical assistants (MAs) are among the fastest-growing occupations in the United States, yet health care employers report high turnover rates and difficulty filling MA positions. Employers are increasingly using apprenticeship to meet emerging workforce needs. This qualitative study examined the perspectives of 14 employers using registered MA apprenticeships in 8 states. The findings revealed motivations for using apprenticeship, perceived benefits to the organization, challenges with implementation, and reflections on successful implementation. We detail how MA apprenticeship is successfully meeting recruitment and training needs in a variety of health care organizations, especially where program support resources are available.